Changing rainfall and its adaptation strategies on tea plantation in West Java, Indonesia - Fatawa, Muhammad Ihsan; Santosa, Edi; Hapsari, Dhika Prita; Krisantini (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Climate change, i.e., changing rainfall refers to drought and excess rainfall, is known to affect the growth and yield of tea production in many regions. However, research on the impact of climate change on tea plantations in Indonesia is still limited. The study aimed to evaluate the impact of changing rainfall on the productivity of tea plantation at Cianjur, West Java. The data was collected from interviews, field data, and company records from April to July 2022. The results showed that changing rainfall of both limited rainfalls during El Nino and excess rainfall during La Nina affected the tea production. Annual tea productivity declined during both climatic events. Shortage of water during El Nino primarily reduced crop growth, while excess rainfall during La Nina reduced the capacity of tea pickers and increased labor for crop maintenance. Failure to adapt to the direct and indirect impacts of climate change could contribute to declining tea production in Indonesia. Thus, comprehensive action is needed including capacity building in human resources, water management, and microclimate adaptation such as shading plants and tolerant clones to sustain tea production under climate change events.